Practices of counter-conduct as a mode of resistance in Middle East women’s life writings - Asl, Moussa Pourya (Penerbit Universiti Kebangsaan Malaysia, 2018)
Middle East women life writings have been downplayed for their oversimplified representations of female subjects as purely passive, submissive and unresisting. This article explores the allegation in three contemporary memoirs by Jean P. Sasson (1992) (the ghostwriter of Saudi princess Sultana), Zainab Salbi (2005) and Manal al-Sharif (2017) who recount similar observations on subordinated women’s daily experiences in phallocentric Arab communities, and whose stories have similarly been the subject of much controversial criticism. In the present study, I aim to examine the practices exercised by marginalized Arab women to destabilize the patriarchal status quo and redefine the established ways of being. To do so, I draw on Michel Foucault’s notion of counter-conduct, often associated with the issues of women and their socio-political and religious position, to identify acts of defiance that are exercised simultaneously with strategies of governmentality through practices of moral self-reflection, or what Foucault describes as the art of being governed differently. The article concludes that in creatively documenting their life stories and through tactical elements such as counter-history, counter-society and reversed obedience, the so-called passive women interrogate the totality of prevailing hierarchies of power, and resist against the unequal society as well as the operating practices of subjugation.